P2Y12-inhibitor clopidogrel promotes collateral artery growth in a murine hindlimb model of arteriogenesis - Elbs, Katharina; Bobrowski, Lisa; Arnholdt, Christoph; Kübler, Matthias; Götz, Philipp; Rohrmoser, Michael R.; Merkus, Daphne; Lasch, Manuel; Deindl, Elisabeth (Biomedicines, 2025)
Background/Objectives: Clopidogrel is a P2Y12 receptor inhibitor commonly used as antiplatelet therapy for patients with cardiovascular occlusive diseases. However, its role in vascular remodeling remains poorly understood. Platelets orchestrate the sterile inflammation in arteriogenesis, an endogenous process to bypass an occluded artery. Therefore, we investigated the impact of P2Y12-inhibition by Clopidogrel on arteriogenesis. Methods: In this study, we utilized a well-established murine hindlimb model of arteriogenesis. To quantify the growth of collateral arteries, we employed laser-Doppler perfusion measurements and immunohistological analysis of growing compared to resting collateral arteries. Additional immunofluorescence and histological stains were conducted to assess immune cell recruitment and activation. Whole-blood flow cytometry was performed to analyze platelet-leukocyte interactions, and complete blood counts were obtained to quantify leukocyte and platelet numbers. Results: The findings of this study demonstrate that Clopidogrel promotes perfusion recovery following the induction of arteriogenesis compared to controls, attributed to elevated levels of proliferating vascular cells. Furthermore, compared to controls, Clopidogrel treatment significantly enhanced platelet-leukocyte interactions, increasing perivascular mast cell recruitment and degranulation, finally resulting in regenerative macrophage accumulation required for collateral artery growth. Conclusions: Clopidogrel treatment boosts arteriogenesis by enhancing the local regenerative inflammation relevant for vascular cell proliferation. Therefore, P2Y12 inhibition may represent a therapeutic option to effectively promote natural bypass growth in patients with cardiovascular occlusive diseases.